Do My Reactions Outweigh My Actions? The Relation between Reactive and Proactive Aggression with Peer Acceptance in Preschoolers - Brenda M. S. da Silva; Guida Veiga; Carolien Rieffe; Hinke M. Endedijk; Berna Güroğlu (Children, 2023)
Aggressive behaviors negatively impact peer relations starting from an early age. However, not all aggressive acts have the same underlying motivations. Reactive aggression arises as a response to an antecedent behavior of someone else, whereas proactive aggression is initiated by the aggressor and is instrumental. In this study, we aim to understand the relation between reactive and proactive aggression and peer acceptance in preschoolers. Parents of 110 children aged between 3 and 6 years old rated their children’s manifestation of reactive and proactive aggressive behaviors. To assess the children’s peer acceptance score within their class, they completed a paired comparisons task. The outcomes confirmed that reactive aggression in particular is negatively related to peer acceptance at the preschool age. Our results provide insights for the needs and directions of future research and interventions.